Green hybrids of poly(lactic) acid - Chong, Jaren Wei Ren (2017)
Polylactic acid (PLA) is plant-derived and a readily biodegradable polymer. As one of the most environmentally friendly polymers in sustainable development, PLA is being studied extensively in the hopes that it may one day replace commercially used polymers which are not environmentally friendly. However, the main drawback of PLA is its low glass transition temperature (Tg), of 60-65oC, and a low heat distortion temperature. The other polymer used in this study is lignin, which is abundant in nature, and is a by-product of the paper manufacturing process. It has great potential as a filler, as well as a thermal and mechanical property modifier for other biopolymers. Integration of lignin and PLA can potentially enhance the performance of the polymers, but due to compatibility issues these two polymers have not been commercialized. The focus of this project is to determine if a blend of PLA and maleic anhydride can improve the physical and thermal properties of a PLA lignin composite. It was found that the addition of the compatibilizer caused the Tg of the blend to decrease, while the viscosity showed a decreasing trend as compatibilizer was added. Additionally, the thermal stability of the blends increased up till 4% compatibilizer. It was concluded that the addition of compatibilizer does have a positive effect on the thermal stability of the blend, while at the same time reducing viscosity.